(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the formation and development of social and economic relations in the Khorezm region and their impact on the New Uzbekistan. Based on historical sources, archival documents, and contemporary economic analyses, the study examines how the socio-economic structures of the region influenced societal development, economic stability, and the implementation of new social policies. The article highlights not only the historical context but also the connection with the ongoing socio-economic reforms in Uzbekistan.